Developing and Refining New Candidate Criteria for Systemic Lupus Erythematosus Classification: An International Collaboration. Issue 4 (22nd February 2018) - Tedeschi, Sara K.; Johnson, Sindhu R.; Boumpas, Dimitrios; Daikh, David; Dörner, Thomas; Jayne, David; Kamen, Diane; Lerstrøm, Kirsten; Mosca, Marta; Ramsey‐Goldman, Rosalind; Sinnette, Corine; Wofsy, David; et al.
Abstract : Objective: To define candidate criteria within multiphase development of systemic lupus erythematosus (SLE) classification criteria, jointly supported by the American College of Rheumatology and the European League Against Rheumatism. Prior steps included item generation and reduction by Delphi exercise, further narrowed to 21 items in a nominal group technique exercise. Our objectives were to apply an evidence‐based approach to the 21 candidate criteria, and to develop hierarchical organization of criteria within domains. Methods: A literature review identified the sensitivity and specificity of the 21 candidate criteria. Data on the performance of antinuclear antibody (ANA) as an entry criterion and operating characteristics of the candidate criteria in early SLE patients were evaluated. Candidate criteria were hierarchically organized into clinical and immunologic domains, and definitions were refined in an iterative process. Results: Based on the data, consensus was reached to use a positive ANA of ≥1:80 titer (HEp‐2 cells immunofluorescence) as an entry criterion and to have 7 clinical and 3 immunologic domains, with hierarchical organization of criteria within domains. Definitions of the candidate criteria were specified. Conclusion: Using a data‐driven process, consensus was reached on new, refined criteria definitions and organization based on operating characteristics. This work will be followed by a multicriteria decision analysis exercise to weight criteria and to identify a threshold score for classification on a continuous probability scale.